2010
DOI: 10.1590/s1516-31802010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for patients diagnosed with pregnancy-associated breast cancer: a paired case-control study

Abstract: CONTEXT AND OBJECTIVE: Previous studies have suggested that the occurrence of pregnancy concomitantly with a diagnosis of breast cancer may affect the evolution of the neoplasia. The present study aimed to compare pregnancy-associated breast cancer (PABC) patients with non-pregnant cancer patients (controls) in relation to the time taken to diagnose the disease, tumor characteristics and mortality. DESIGN AND SETTING:A retrospective, paired case-control study was conducted at the Hospital da Santa Casa de Mise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 16 publications
11
38
0
Order By: Relevance
“…Moreover, our results are in accordance with those recently published by Azim et al [18]; in this well designed case-control study, PABC patients exhibited a poorer prognosis compared to age- and stage-matched controls, whilst there was no difference in tumor features between the 2 groups. In addition, our study seems in accordance with numerous unmatched studies which pointed through multivariate adjustment to an independent role of pregnancy, controlling for stage [19,20,21]. On the other hand, apart from smaller studies, the present report is in line with a recent population-based cohort study by Johansson et al including 15,721 women, which essentially confirmed the findings regarding pregnancy in a large population sample [24]; however, it should be stressed that the authors did not provide any data regarding prognostic parameters of the breast cancers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, our results are in accordance with those recently published by Azim et al [18]; in this well designed case-control study, PABC patients exhibited a poorer prognosis compared to age- and stage-matched controls, whilst there was no difference in tumor features between the 2 groups. In addition, our study seems in accordance with numerous unmatched studies which pointed through multivariate adjustment to an independent role of pregnancy, controlling for stage [19,20,21]. On the other hand, apart from smaller studies, the present report is in line with a recent population-based cohort study by Johansson et al including 15,721 women, which essentially confirmed the findings regarding pregnancy in a large population sample [24]; however, it should be stressed that the authors did not provide any data regarding prognostic parameters of the breast cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies did not suggest any significant associations [7,8,9,10,11,12,13], whereas others attributed any detrimental effects solely on the delayed diagnosis of tumors in pregnancy [14,15,16,17,18]. On the contrary, some studies pointed to the opposite direction, indicating an independent poor prognostic role of pregnancy [19,20,21]. From a methodological point of view, the aforementioned may imply that the elucidation of the effects mediated by pregnancy may to a certain extent be challenging, as the advanced stage of tumors diagnosed during pregnancy seems to represent a confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…As far as outcome of PABC is concerned data are conflicting: some authors showed no difference in outcome of PABC and non-PABC cases [14,16,24], while others consider PABC as having unfavorable prognosis [1,[7][8][9]. In a recent metaanalysis of 30 studies, Azim et al found that PABC patients had poor overall survival especially if breast cancer was diagnosed within 1 year postpartum [25].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of PABC is more often reported as being unfavorable [1,[7][8][9][10]. Whether this poor prognosis is related to pregnancy or mainly due to the young age of patientswhich in itself is known to be a poor prognostic factor [11] -is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic abortion was a response to the belief that the hormonal milieu of pregnancy resulted in the poor outcome. Some studies indicate that prognosis in advanced-stage cancer is worse in the pregnancy-associated group than in a stage-matched nonpregnant group 15,48 , especially for women more than 35 years of age and for those diagnosed within 1 year postpartum 20,21,24,28,53 .…”
Section: 12mentioning
confidence: 99%